Effect of illumination, noise and text/background colour on spontaneous eye blink rate. - Hasan, Syed Noorul; Muzammil, Mohammad; Khan, Abid Ali (Theoretical Issues in Ergonomics Science, 2011)
This study investigated the effect of varying levels of illumination, noise and colour combination on blink rate for subjects of different age groups (21–30, 31–40 and 41–50 years) having Internet exposure duration of less than 2 h/day (category 1) and more than 2 h/day (category 2). The pseudo reading task was designed as a software program to investigate the reading task performance. Results showed that the text–background colour combination was significant on the change in spontaneous eye blink rate (SEBR) values on both categories of users for age groups of 21–30 and 41–50 years. The effects of illumination and noise were not significant for subjects of all categories and age levels except for age group of 31–40 years with Internet exposure duration of more than 2 h/day, where illumination was observed to be significant. The results of the study further showed that ambient illumination did not affect significantly the SEBR values for every age group investigated in this research.